Application of Health Technology Assessment (HTA) to Evaluate New Laboratory Tests in a Health System: A Case Study of Bladder Cancer Testing. (5th November 2020) - Landaas, Erik J.; Eckel, Ashley M.; Wright, Jonathan L.; Baird, Geoffrey S.; Hansen, Ryan N.; Sullivan, Sean D.
We describe the methods and decision from a health technology assessment of a new molecular test for bladder cancer (Cxbladder), which was proposed for adoption to our send-out test menu by urology providers. The Cxbladder health technology assessment report contained mixed evidence; predominant concerns were related to the test's low specificity and high cost. The low specificity indicated a high false-positive rate, which our laboratory formulary committee concluded would result in unnecessary confirmatory testing and follow-up. Our committee voted unanimously to not adopt the test system-wide for use for the initial diagnosis of bladder cancer but supported a pilot study for bladder cancer recurrence surveillance. The pilot study used real-world data from patient management in the scenario in which a patient is evaluated for possible recurrent bladder cancer after a finding of atypical cytopathology in the urine. We evaluated the type and number of follow-up tests conducted including urine cytopathology, imaging studies, repeat cystoscopy evaluation, biopsy, and repeat Cxbladder and their test results. The pilot identified ordering challenges and suggested potential use cases in which the results of Cxbladder affected a change in management. Our health technology assessment provided an objective process to efficiently review test performance and guide new test adoption. Based on our pilot, there were real-world data indicating improved clinician decision-making among select patients who underwent Cxbladder testing.